The effect of transmyocardial laser revascularization on anginal symptoms and clinical results in patients with incomplete surgical revascularization - (:unkn) unknown (My University, 2009)
OBJECTIVES: We evaluated the effect of transmyocardial laser revascularization (TMR) on anginal symptoms and clinical results in patients in whom coronary artery bypass grafting (CABG) surgery was not sufficient to provide complete revascularization. STUDY DESIGN: This retrospective study included 45 patients who underwent CABG surgery with incomplete revascularization between 2003 and 2006. Of these, 35 patients (mean age 61.7 years) had CABG alone, while 10 patients (mean age 62 years) underwent TMR at the same session as an adjunct to CABG. All the patients were assessed by transthoracic echocardiography and myocardial perfusion scintigraphy at three months and after a mean follow-up period of 22.3+/-6.1 months. Anginal symptoms were assessed using the CCS (Canadian Cardiovascular Society) classification system. RESULTS: Preoperative variables were similar in both groups. All the patients were symptomatic preoperatively with mean CCS scores of 2.6+/-0.5 and 2.3+/-0.8 in the TMR and CABG-alone groups, respectively. The duration of cardiopulmonary bypass (CPB) was significantly longer in the TMR group (p=0.022). During weaning from CPB, the need for inotropic support was significantly less in the TMR group (10% vs. 48.6%; p=0.034). While there was no early mortality, late mortality occurred in three patients (1 in TMR, 2 in CABG-alone groups; p=0.329). At three months, 50% (n=5) of the TMR patients were asymptomatic, compared to 14.3% (n=5) in the CABG-alone group (p=0.016). Patients in the TMR group had significantly lower CCS angina scores at three months (1.2+/-0.6 vs. 2.2+/-0.7; p=0.001) and at the end of the follow-up (1+/-0.6 vs. 2+/-0.7; p=0.001). There were no significant differences between the two groups with regard to the findings of myocardial perfusion scintigraphy and echocardiography. CONCLUSION: Patients with incomplete surgical revascularization benefit from TMR in terms of decreased need for inotropic support during weaning from CPB and short- and mid-term relief of angina symptoms.
Keywords: Female; Humans; Treatment Outcome; Male; Follow-Up Studies; Cardiopulmonary Bypass; Echocardiography; Laser Therapy; Coronary Circulation; Coronary Artery Bypass; Angina Pectoris